Assessing iron and zinc nano-fertilizers on rice growth: comparative study using drought tolerance indices and graphic analysis - M. Jafarsalehi; P. Mazloom; M. S. Daliri; S. A. Mousavi; A. Eftekhari (Brazilian Journal of Biology)
Abstract Rice (Oryza Sativa L.) is the main food of about half of the people in the world. In order to compare the treatments of iron and zinc nanofertilizers in three irrigation conditions, an experiment was conducted in the form of a split plot based on randomized complete blocks in three replicates on the Tarem Hashemi rice variety. The results of compound analysis showed that the effect of irrigation regime and zinc nano-fertilizer in all traits and the effect of iron nano-fertilizer in all traits except thousand seed weight have significant differences. In the review of the selected treatments for cultivation based on drought tolerance indices, treatments Tr2, Tr5 and Tr11 were selected as suitable treatments for cultivation in conditions of lack of humidity. The results obtained from the polygon diagram indicated that the Tr7 treatment can be selected as a suitable treatment in all three irrigation conditions. In the analysis of the results obtained from the ranking chart of the treatments in terms of traits, the Tr3 treatment was selected as a stable treatment in rice cultivation. In the examination of the diagram to identify the most appropriate treatment based on the ideal treatment, treatments Tr3 and Tr6 under normal conditions and treatment Tr2 under both conditions of irrigation stress were selected as optimal treatments. The grouping of treatments based on traits also showed that Tr8 and Tr9 treatments were very similar in terms of reaction to traits. In general, it can be concluded that in different irrigation conditions, according to the soil quality of the fields, the effect of zinc nano-fertilizer at medium concentration levels can have a favorable effect on increasing the quality of quantitative and qualitative traits of this plant, and low concentration levels of nano-fertilizer Iron can have a positive effect on increasing the quality of the product in the condition of lack of humidity.